Struktur Aktansial Greimas Dalam Novel Dompet Ayah Sepatu Ibu Karya J.S. Khairen - Fahmi, Ismail (Maliki Interdisciplinary Journal, 2025)
This research examines the narrative patterns in the novel Dompet Ayah Sepatu Ibu by J.S. Khairen using Algirdas Julien Greimas’s narratological analysis. The study focuses on the dynamic relationships among characters, particularly Asrul as the main subject in the storyline. Greimas’s actantial theory is employed to map the narrative roles, subject, object, sender, receiver, helper, and opponent, that shape the structure of the story. The research applies a formal method using reading and note-taking as data collection techniques, along with Miles and Huberman’s analytical framework. The findings reveal seven actantial structures in the novel, four of which are complete while the other three are incomplete. These actantial structures demonstrate that the interactions among characters not only determine the plot but also reflect the novel’s central themes, such as family values, struggle, and sacrifice. An in-depth analysis of character relationships shows that the dynamics of conflict, goals, and resolutions faced by the main characters construct a complex narrative that deeply engages readers emotionally. These findings emphasize the crucial role of actantial structures as a fundamental framework for understanding narrative relations in literary works. Therefore, this study contributes to expanding narratological research in Indonesian literature, particularly in the works of J.S. Khairen, which are rich in values and meaning.